2008
DOI: 10.1021/bi800139w
|View full text |Cite
|
Sign up to set email alerts
|

TATA-Binding Protein Recognition and Bending of a Consensus Promoter Are Protein Species Dependent

Abstract: The structure and behavior of full-length human TBP binding the adenovirus major late promoter (AdMLP) have been characterized using biophysical methods. The human protein induces a 97° bend in DNA AdMLP. The high-resolution functional data provide a quantitative energetic and kinetic description of the partial reaction sequence as native human TBP binds rapidly to a consensus promoter with high affinity. The reaction proceeds with successive formation of three bound species, all having strongly bent DNA, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 46 publications
1
54
0
Order By: Relevance
“…Our model suggests TBP shows little discrimination between sequences during association and sequence specificity is defined by the sequence's kinetic stability. This agrees with the observation that the first phase of TBP binding (in the three-step model) is independent of TBP concentration, as would be expected in our model (42). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our model suggests TBP shows little discrimination between sequences during association and sequence specificity is defined by the sequence's kinetic stability. This agrees with the observation that the first phase of TBP binding (in the three-step model) is independent of TBP concentration, as would be expected in our model (42). …”
Section: Discussionsupporting
confidence: 93%
“…However, to elucidate the precise conformational states for each DNA, more powerful techniques are needed. For example, previous studies suggested that two or more different intermediate states are present during binding of TBP to a minimal TATA-DNA (13,16), while more recent spFRET studies on human TBP indicate a two-state system (37,42). To test whether flanking DNA influences the formation of any intermediate states, we used single-pair FRET (spFRET) spectroscopy (43) to resolve the specific DNA conformations induced by TBP binding.…”
Section: Resultsmentioning
confidence: 99%
“…Additional controls to correct for spectral overlap must be performed (see below). While FRET has been utilized to measure high-affinity interactions inferred from intramolecular distance changes (9,23,24), it has not been widely used for measuring intermolecular interactions between labeled components. Several recent descriptions for quantitative intermolecular FRET affinity measurements have been published; however these experiments rely upon high probe concentrations and are not amenable to high-affinity interactions (11,25,26).…”
Section: Resultsmentioning
confidence: 99%
“…We monitored the dynamics of the TBP–DNA TATA interaction on the single-molecule level using a FRET signal as readout that allowed us to follow the TBP-induced bending of the promoter DNA (27) (Figure 1C). As TBP binding is inseparably connected to DNA bending, this assay provides information about both complex formation and DNA bending (22). In order to ensure biological relevant temperatures for the archaeal systems, we equipped our single-molecule total internal reflection fluorescence (TIRF) setup with a heating module that allowed temperature-controlled measurements up to 60°C.…”
Section: Introductionmentioning
confidence: 99%